The Effect Of Organizational Culture and Work Life Balance On Employee Performance and Job Satisfaction as a Mediator - Nadia Dwi Harini; Novriadi Fernando; M Havidz Aima; Yulasmi Yulasmi (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the influence of organizational culture and work-life balance on employee performance with job satisfaction as an intervening variable at the Agam Regency Land Office Materials and methods. The population in this research consisted of 70 employees, and the sampling technique used was total sampling, making the entire population the sample. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with SmartPLS 3. Results. The results showed that organizational culture had a positive and significant effect on job satisfaction, while work-life balance also had a positive and significant effect on job satisfaction. Furthermore, organizational culture was found to have a positive and significant effect on employee performance, whereas work-life balance did not have a significant direct effect on employee performance. Job satisfaction positively and significantly influenced employee performance. In addition, job satisfaction was proven to mediate the effect of organizational culture and work-life balance on employee performance. Conclusions. organizational culture and work-life balance play an important role in enhancing job satisfaction, which subsequently improves employee performance at the Agam Regency Land Office